Australian health professions student use of social media - Usher, K.; Woods, C.; Casella, E.; Glass, N.; Wilson, R.; Mayner, L.; Jackson, D.; Brown, Janie; Duffy, E.; Mather, C.; Cummings, E.; Irwin, P. (Elsevier BV, 2014)
Increased bandwidth, broadband network availability and improved functionality have enhanced the accessibility and attractiveness of social media. The use of the Internet by higher education students has markedly increased. Social media are already used widely across the health sector but little is currently known of the use of social media by health profession students in Australia. A cross-sectional study was undertaken to explore health profession students' use of social media and their media preferences for sourcing information. An electronic survey was made available to health profession students at ten participating universities across most Australian states and territories. Respondents were 637 first year students and 451 final year students. The results for first and final year health profession students indicate that online media is the preferred source of information with only 20% of students nominating traditional peer-reviewed journals as a preferred information source. In addition, the results indicate that Facebook® usage was high among all students while use of other types of social media such as Twitter® remains comparatively low. As health profession students engage regularly with social media, and this use is likely to grow rather than diminish, educational institutions are challenged to consider the use of social media as a validated platform for learning and teaching.